Association of Slipped Capital Femoral Epiphysis With Panhypopituitarism Due to Pituitary Macroadenoma: A Case Report - James B. Harris; Bhuvana Sunil MD; Michael K. Ryan MD; Giovanna Beauchamp MD (SAGE Publishing, 2021)
Slipped capital femoral epiphysis (SCFE) commonly occurs in overweight or obese adolescents, but can also be associated with endocrine disorders including hypothyroidism, pituitary tumors, and growth hormone deficiency. In this article, we present a case of panhypopituitarism that initially presented with SCFE. A 16-year-old male presented with right SCFE. After a right hip open reduction and percutaneous pinning procedure, findings of skeletal maturity that lagged behind his chronologic age and a delayed Tanner stage resulted in a referral to an endocrine specialist. Endocrine laboratory evaluation identified elevated prolactin levels (1493 ng/mL), hypogonadotropic hypogonadism, and central adrenal insufficiency as evidenced by low morning cortisol level of 1.0 µg/dL. Magnetic resonance imaging revealed a large pituitary T2 isointense mass measuring 1.8 × 2.7 × 2.3 cm. The patient was diagnosed with panhypopituitarism due to a pituitary macroadenoma. Multidisciplinary collaboration for treatment of this patient consisted of oral cabergoline, oral levothyroxine, oral hydrocortisone therapy, intramuscular testosterone therapy, and a prophylactic closed reduction percutaneous pinning of the left hip due to high risk of also developing SCFE of the left hip. Panhypopituitarism should be considered as a diagnosis after atypical presentations of SCFE. In our case, an astute clinical assessment resulted in prompt endocrine referral and management of panhypopituitarism. Our report highlights the importance of multidisciplinary collaborations to guarantee early detection of endocrinopathies in patients with SCFE undergoing surgical interventions in order to avoid potential complications, such as adrenal crisis during surgery.